Weighted empirical FCLT for weakly dependent processes - Juodis, Mindaugas (Lietuvos matematikos rinkinys, 2005)
This paper provides a weak convergence theorem for weighted empirical processes of a stationary sequence under a new weak dependence condition introduced by P. Doukhan and S. Louhichi.